2019
DOI: 10.3390/nu11112586
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Mechanism of Polymerized Anthocyanin from Grape-Skin Extract on High-Fat-Diet-Induced Nonalcoholic Fatty Liver Disease

Abstract: We investigated the therapeutic potential of polymerized anthocyanin (PA) on a nonalcoholic fatty liver disease (NAFLD) model in mice. C57BL/6 mice were fed a high-fat diet (HFD) for 8 weeks to establish the NAFLD mouse model and randomly divided into four groups: control diet (con), NAFLD mice treated with saline (NAFLD), NAFLD mice treated with PA (PA), and NAFLD mice treated with orlistat (Orlistat) for four weeks. Mice were euthanized at the end of the four weeks. Total cholesterol (TC) and triglyceride (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 73 publications
(77 reference statements)
1
30
0
Order By: Relevance
“…In addition, in vivo studies also showed that the oral administration of resveratrol and anthocyanin extracted from grape improved lipid metabolism, oxidative stress, and inflammation in the NAFLD mouse model by downregulating PPAR- γ while upregulating Nrf2 and SIRT1 signaling pathways, accompanied by decreasing the expression of fatty acid synthase (FAS) and sterol regulatory element-binding transcription factor 1c (SREBP-1c) [ 81 , 84 ]. Besides, the consumption of tomato juice could alleviate NAFLD in Sprague-Dawley (SD) rats by increasing the abundance of Lactobacillus and diminishing the ratio of acetate to propionate [ 85 ].…”
Section: Mechanisms Of Plant-based Foods and Their Bioactive Compomentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, in vivo studies also showed that the oral administration of resveratrol and anthocyanin extracted from grape improved lipid metabolism, oxidative stress, and inflammation in the NAFLD mouse model by downregulating PPAR- γ while upregulating Nrf2 and SIRT1 signaling pathways, accompanied by decreasing the expression of fatty acid synthase (FAS) and sterol regulatory element-binding transcription factor 1c (SREBP-1c) [ 81 , 84 ]. Besides, the consumption of tomato juice could alleviate NAFLD in Sprague-Dawley (SD) rats by increasing the abundance of Lactobacillus and diminishing the ratio of acetate to propionate [ 85 ].…”
Section: Mechanisms Of Plant-based Foods and Their Bioactive Compomentioning
confidence: 99%
“…Besides, the administration of anthocyanin extracted from sweet cherry could alleviate NAFLD in HepG2 cells and LO2 liver cells through inducing autophagy by downregulating phosphorylation of the mammalian target of rapamycin (mTOR) and protein kinase B (Akt), while upregulating the phosphorylation of AMPK [83]. In addition, in vivo studies also showed that the oral administration of resveratrol and anthocyanin extracted from grape improved lipid metabolism, oxidative stress, and inflammation in the NAFLD mouse model by downregulating PPAR-γ while upregulating Nrf2 and SIRT1 signaling pathways, accompanied by decreasing the expression of fatty acid synthase (FAS) and sterol regulatory element-binding transcription factor 1c (SREBP-1c) [81,84]. Besides, the consumption of tomato juice could alleviate NAFLD in Sprague-Dawley (SD) rats by increasing the abundance of Lactobacillus and diminishing the ratio of acetate to propionate [85].…”
Section: Beneficial Bioactive Compounds From Coffee In Relationmentioning
confidence: 99%
“…Total RNA was collected from mice livers, and epididymal adipose tissues, and qPCR was conducted, as described previously [ 19 ]. PCR reactions were carried out using AccuPower ® PCR PreMix (Bioneer, Chungwon, Korea) and a Veriti™ 96-Well Thermal Cycler (Applied Biosystems, Foster City, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…The first strand of complementary DNA (cDNA) was synthesized using Superscript II reverse transcriptase (Invitrogen). The conditions for RT-PCR were similar to those previously described [ 45 ]. Quantitative real-time PCR was carried out using a Thermal Cycler Dice TP850 (Takarabio Inc., Shiga, Japan) according to the manufacturer’s protocol.…”
Section: Methodsmentioning
confidence: 99%